Nephrology nurses’ views in giving a dietary recommendation for dialysis patients: An interview study - Hj Emran, Siti Norhayati; Zolkefli, Yusrita (Belitung Nursing Journal, 2021)
Background: Nutrition in dialysis patients plays an essential role in their life. Diet in dialysis patients are catered individually and applied according to the situation of the patients. A dietary recommendation is vital to dialysis patients, and nephrology nurses help patients understand the reasoning behind the dietary restrictions enforced. Objective: This paper aimed to explore nephrology nurses’ views in giving dietary recommendations for dialysis patients. Methods: In this descriptive qualitative study, one focus group discussion (n = eight nurses) and four individual interviews in one Renal Centre in Brunei Darussalam was conducted through purposive sampling. This interview took place between October 2020 and December 2020. Results: Three major themes were identified: (1) Approaches in giving dietary information, (2) Getting patients to follow a diet plan, and (3) Negotiating with patients. Conclusion: The importance of nephrology nurses in improving patient care, particularly in providing dietary recommendations to dialysis patients, cannot be overstated. They adopted different approaches, including negotiating with patients and using available resources to ensure that patients followed the dietary recommendations. However, they believe their current method and strategy for offering dietary recommendations to dialysis patients could be improved.